Promoting Computational Thinking Through Pedagogical Competence and Scientific Capability: The Mediating Role of Locus of Control - Yulita Pujiharti; Amanah Agustin; Raya Sulistyowati; Mukarom; Loesita Sari (Yayasan Nurul Yakin Bunga Tanjung, 2026)
Society 5.0 demands computational thinking (CT) skills among university students, particularly prospective economics teachers. This study examines how pedagogical competence and scientific capability key competencies of pre-service teachers influence CT, with locus of control (LOC) as a mediator. Data were collected via cross sectional survey from 375 economics education students (semester 5-8) across five Indonesian state universities (Java region) using partial least squares structural equation modeling (PLS-SEM) grounded in Rotter's LOC theory (1966) and Bandura's Social Cognitive Theory (1997). Findings reveal pedagogical competence (β=0.929, p<0.01) and scientific capability (β=0.148, p<0.05) significantly predict CT directly, while LOC partially mediates both relationships (H6: β=1.820, p<0.001; H7: β=0.148, p<0.01). This study offers novel theoretical contributions by validating LOC mediation in non-STEM economics education context, unique to Indonesia's collectivist culture. Practically, findings inform teacher education programs (PPG/PGS) to integrate CT pedagogy modules that target the development of internal LOC in learning, and prepare educators to face the challenges of the digital economy.